O trágico como limiar do desencanto: o apocalipse em O livro dos homens sem luz, de João Tordo - Ruy, Igor Fernando (Universidade Federal de São Carlos, 2020)
This essay presents the sensations of the end of the world in the novel O livro dos homens sem luz (2004), by the contemporary Portuguese writer João Tordo (1975-). At first, it approaches the Portuguese author in the opening, mentioning his strategy of literary insertion, through a universal thematic of disenchantment with the human condition, whose strategy of rereading of the past allows a different and less utopian look at the advances in contemporary times. This perception obviously passes through artistic production and, thus, realization in literature, through the exercise of verisimilitude with fiction, the utopian impact of a demand for a social transformation of well-being that has not been completely consolidated. As a result, this essay deals with the construction of this theme through the tragic as a conductive element of a dysphoric action in postmodernity. It discusses the configuration of the end of the world feelings based on losses that lead to the tragic action. João Tordo’s novel, therefore, leads to a reflection on the representation of space and time in the narrative and the conditioning forces in the elaboration of the end of the world, with triggering processes of the type of conduct in the presence of tragic action, in addition to the tendency to rupture with the social ordering processes, determined in the moral sphere, thus thematizing an anti-utopian discourse. Finally, the network of ambiences and catastrophic environments result in a critical look at social relations that, although configured in the fictional scope, reflects the disbelief in the resolution of the frustrations interposed in daily life, establishing melancholy as a connecting thread to the notion that we are near the end of the world.
The tragic as the threshold of disenchantment: the apocalypse in O livro dos homens sem luz, by João Tordo
Keywords: Fim do mundo; Trágico; Ficção portuguesa contemporânea; João Tordo; End of the world; Tragic; Contemporary Portuguese fiction; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS; LINGUISTICA, LETRAS E ARTES::LETRAS::OUTRAS LITERATURAS VERNACULAS; LINGUISTICA, LETRAS E ARTES::ARTES